Effect of protein immunogenicity and PEG size and branching on the anti-PEG immune response to PEGylated proteins. (January 2017) - Wan, Xue; Zhang, Juankun; Yu, Weili; Shen, Lijuan; Ji, Shaoyang; Hu, Tao
Graphical abstract: Highlights: Anti-PEG immunity is strongly affected by the size and the number of PEG. Conjugation with BSA can decrease the anti-PEG immunity to PEGylated TT. Anti-PEG immunity is strongly affected by the immunogenicity of proteins. Abstract: PEGylation has successfully improved the pharmacological properties of therapeutic proteins. However, polyethylene glycol (PEG) has been burdened by immunogenicity that renders a negative clinical effect on therapeutic proteins. The anti-PEG immune response to PEGylated proteins possibly depends on the nature of proteins and the conjugated methoxy PEG (mPEG). Thus, it is necessary to investigate the effects of protein immunogenicity, the extent of PEGylation, the molecular weight (Mw), and the branching of mPEG on the anti-PEG immune response. Ovalbumin, tetanus toxoid (TT), TT–TT conjugate, and TT–bovine serum albumin conjugate were used as target proteins. PEGylated proteins with different extents of PEGylation were obtained by fractionation of the PEGylated TT with size exclusion chromatography. The PEGylated proteins with different Mw and branching of mPEG were obtained by modification of TT with linear mPEG (5 kDa and 20 kDa) and branched mPEG (20 kDa). The PEGylated proteins elicited high levels of anti-PEG antibodies (predominantly IgM and IgG1). The anti-PEG immune response depended on the immunogenicity of proteins, the extent of PEGylation, and the Mw of mPEG. In contrast, branching of mPEG had an insignificant effect on the anti-PEG immune response to the PEGylated proteins.